Village homes : a community by design - Francis, Mark, 1950- 4 0 16; 5 Landscape Architecture Foundation (U.S.) (Washington, DC : Island Press, 2003)
Profiles the Village Homes neighborhood in Davis, California, analyzing the house designs and discussing why the development was such a success and why, despite that success, it has never been replicated.
Landscape Architecture Foundation.
Includes bibliographical references (p. [85]-87) and index.
Adult;Adult.
Keywords: 2 -- 0; 6; Landscape architecture;City planning -- Davis (Calif.);Davis (Calif.) -- Case studies.;Case studies; Davis (Calif.) -- Case studies; 2